Architectural memory and forms of its existence - Remizova, Olena (Journal of Architecture and Urbanism, 2020)
The article attempts to highlight the traces of memory in the theory, history and practice of architecture. The subject of research is the existing forms of memory in architecture. It is traditionally accepted that the “history of architecture” as a science is the main repository of knowledge about the evolution of architecture. Facts and artifacts, descriptions of monuments and cities are retained in it. The article emphasizes that the traditional “history of architectural objects” is not the only form of memory. Another equally important and complicated aspect of the architectural memory is detected during the decoding of the evolution of project activity and its language. Analysis of the evolution of architecture allowed us to differentiate the epochs in which historical thinking prevails: the Renaissance, Romanticism, Eclecticism, Art Deco, Postmodernism. They are characterized by such ways of thinking as dialogical, historical and typological, historical and associative. They are opposed to design approaches in which abstract thinking dominates (Art Nouveau and Modernism). The article shows that the concept of architectural memory has many shades and manifests itself in a variety of different forms of professional consciousness. As historical knowledge, memory exists in such forms as: a chronological description, science of history, evolutionary studies, catalog of styles, museum, archive. In designing and its language, memory is represented in such forms as canon, dialogue with bygone era, norm, architectural fantasy, remembrance, historical association, reconstruction, restoration and others. It is shown that the most important way of storing and transferring information is the architectural language and compositional logic. Postmodern consciousness raised the problem of loss of memory and the development of architectural language and communication of culture.